SISTEM PENUNJANG KEPUTUSAN PENENTUAN BUAH TERBAIK MENGGUNAKAN METODE TOPSIS BERBASIS WEB (Studi Kasus: Toko Juz FoodyMoody) - Nufel Pahlevi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The decision Support System (Decision Support System) is designed to produce various alternatives offered to decision makers, because most of the decisionmaking process is a form of selection from various alternatives to be selected, through certain mechanisms, in the hope of producing a good decision. The method used for decision selection is the Technique For Order Preferences by Similarity to Ideal Solution (TOPSIS) which can help find the optimal solution or alternative for a problem that will be displayed on a website-based basis. This method can help decisionmakers in situations where there are many alternative decisions with several criteria, for selecting the best fruit at the FoodyMoody fruit juice shop.